Large Bowel Obstruction in a Young Woman Simulating a Malignant Neoplasm: A Case Report of Actinomyces Infection - R. Nissi; R. B. Blanco Sequeiros; E. Lappi-Blanco; H. Karjula; A. Talvensaari-Mattila (Case Reports in Obstetrics and Gynecology)
Pelvic and intra-abdominal Actinomycosis can be difficult to diagnose preoperatively and it may also mimic many other diseases, including malignancies. We present a patient with pelvic Actinomycosis probably caused by a long-standing intrauterine device (IUD). We emphasize the challenges in diagnostic process and stress that though a rare disease, intra-abdominal Actinomycosis should be suspected in cases with intra-abdominal mass of uncertain etiology. The early recognition may spare the patient from extensive surgical operation.